CRIMINAL RESPONSIBILITY FOR THE CRIMINAL ACT OF UNAUTHORIZED USE OF STATE LAND (Study in Desa Tadukan Raga Kecamatan STM Hilir) - M. Ardiansyah Bancin (RADJA PUBLIKA, 2026)
Unauthorized possession of state land is a form of crime that results in state losses and disrupts orderly administration and regional spatial planning. This phenomenon is widespread in various regions, including in Tadukan Raga Village, STM Hilir District, Deli Serdang Regency. This crime raises profound legal issues related to the criminal liability of the perpetrators and the effectiveness of law enforcement by authorized officials. This problem is examined in a study entitled Criminal Liability for the Criminal Act of Land Acquisition